337 Homeostatic signals promote differentiation of memory T cell subsets that mediate sensitive IFN - Sunder Bharadwaj, Nikhila Sham; Gumperz, Jenny (Journal for immunotherapy of cancer, 2023)
BackgroundT cell derived IFN-γ plays a critical role in orchestrating effective anti-tumor response post hematopoietic transplantation. While acquisition of IFN-γ by naive T cells via pathogenic stimulation is well documented, little is known about the effects of homeostatic signals that cells encounter during lymphopenia, a central feature of clinical transplantation protocol.MethodsUsing an in-vitro culture system we investigated how naïve human T cells acquire the capacity to produce IFN-γ when exposed to homeostatic signals in a pathogen independent manner.ResultsWe find that in the absence of strong antigenic stimulation, exposure to homeostatic signals provided by autologous antigen presenting cells (APCs) leads to the rapid differentiation of two distinct T cell populations. One population resembled stem cell memory T cells (TSCM) that co-expressed CD45RA, CD95 and retained expression o transcription factor TCF-1. The other subset differentiated into memory phenotype (MP) cells, showing upregulated CD45RO, IL-12 receptor β2 (IL12R β2) expression and transcription factor T-bet. Functionally, both MP and TSCM cells derived from such pathogen independent activation were more efficient in producing IFN-γ to weak agonism provided by neoplastic autologous B cells. Further analysis revealed that both MP and TSCM cells have elevated oxidative metabolism and increased metabolic reserves. While MP cells were able to rapidly produce IFN-γ in response to a 4hr PMA/ionomycin stimulation, TSCM subset lacked this ability. In contrast TSCM cells showed enhanced capacity to strongly re-proliferate.ConclusionsA key area of future studies will characterize how MP and TSCM subsets mediate anti-tumor function in-vivo. Results from our study provide insight into cellular and metabolic processes that underline better T cell effector responses and will enable development of approaches to improve efficacy of T cell-based immunotherapies.Ethics ApprovalHuman tissue samples were acquired and handeled in accordance with UW-Madison Minimal Risk IRB protocol 2018–0304, or as specified under IRB-certified Not Human Subjects Research Exemptions 2017–0870 and 2023–0392.